Soluble Recombinant Hemagglutinin Protein of H1N1pdm09 Influenza Virus Elicits Cross-Protection Against a Lethal H5N1 Challenge in Mice - Yamada, Shinya; Yasuhara, Atsuhiro; Kawaoka, Yoshihiro (Frontiers in Microbiology, 2019)
Currently, influenza vaccines are produced using embryonated chicken eggs. Recently, recombinant influenza vaccines have been developed as a potential alternative to egg-grown vaccines. In this study, we evaluated the efficacy of soluble recombinant hemagglutinin (HA) protein produced in human cell culture (Expi293F cells) as an influenza vaccine against homosubtypic and heterosubtypic influenza virus challenges in mice. Mice were immunized intramuscularly with purified soluble HA protein of H1N1pdm09 virus and then challenged with a lethal dose of H1N1pdm09, seasonal H3N2, or highly pathogenic avian influenza (HPAI) H5N1 virus. Vaccinated mice showed better morbidity than mock-vaccinated mice following H1N1pdm09 challenge. By contrast, all mice died following H3N2 challenge. Interestingly, all vaccinated mice survived challenge with H5N1 virus, whereas all mock-vaccinated mice died. These results suggest that intramuscular immunization with recombinant HA proteins produced in Expi 293F cells could be of value in influenza vaccine strategies.